PENERAPAN SANKSI PIDANA PENYALAHGUNAAN NARKOTIKA YANG DILAKUKAN ANAK DIBAWAH UMUR ( Studi Perkara No.18/Pid.Sus-Anak/2016/PN Smg ) - Barokah Barokah (Jurnal Ilmiah Dinamika Hukum, 2019)
The application of sanctions for children is not the same as the application of sanctions for adults, criminal sanctions imposed on children are based on justice, truth, welfare, and the child's future, children have special characteristics and characteristics that require guidance in order to ensure their physical and mental growth as a whole. , harmonious and balanced because children are the most important pillar in determining the fate of the nation and state in the future. An addict or narcotic abuser from a legal perspective is also a criminal offender. In this study, the authors raised several problems, namely How to Implement Criminal Sanctions Against Children of Narcotics Abusers and How Judges Considerations in Deciding Narcotics Abusers in Decision No.18 / Pid.Sus-Anak / 2016 / PN Smg. The research method used in this research is in concreto. This writing aims to explain the Application of Criminal Sanctions Against Narcotics Abuse Children and Judge Considerations in Dropping Decisions Against Narcotics Abuse in Decision No.18 / Pid.Sus-Anak / 2016.PN Smg, the defendant is sentenced to sanctions for actions namely by medical rehabilitation and social rehabilitation . The sanctions obtained by narcotics criminal offenders in decision No.18 / Pid.Sus-Anak / 2016 / PN Smg are in accordance with existing regulations in Indonesia, apart from being accompanied by a person / guardian, the defendant is accompanied by a legal advisor, namely Rizka Abdurrahman SH, MH, during the examination process of the defendant did not receive discriminatory treatment / distinction, the judge in passing the verdict for the defendant has considered things that are burdensome and lighten and consider everything that is best for the child. Keywords : Children, Narcotics, Abuse, Application of Criminal Sanctions